Cyber War and Civil Protection in the Perspective of International Humanitarian Law: Legal Challenges and Innovations in the Digital Age - Taufik Nur Cahyanto; Adietya Yuni Nurtono; Tarsisius Susilo; Budiman Marpaung; Budi Saroso (Jurnal Impresi Indonesia, 2025)
Cyber warfare is a form of warfare that is explicitly unmanageable by existing international law. While most experts agree that legal restrictions should apply to this phenomenon. Cyber warfare has also presented unprecedented new challenges to the application of International Humanitarian Law (IH), particularly in terms of the protection of civilians. As digital infrastructure becomes an essential part of civilian life and military operations, the basic principles of HHI such as distinctiveness, proportionality, and prudence face significant obstacles in cyberspace. This article analyzes a variety of emerging legal ambiguities, including attribution issues, dual-use infrastructure, and non-physical impacts on civilians. In addition, this article explores legal innovations such as the reinterpretation of existing principles, the role of the Tallinn Manual, as well as the possibility of developing new legal instruments that are more adaptive to digital reality. The study concludes with policy recommendations to strengthen civil protection and enrich the cyber law architecture through multilateral cooperation and the development of new legal norms.